Layanan Pengelola Perpustakaan dalam Melayani Pemustaka Disabilitas di Perpustakaan Sekolah Luar Biasa (SLB) Kota Batusangkar - Adelson, Randa; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discussed about the attitude in serving the library manager disabilities in school library (SLB) Batusangkar City. This study aims to: (1) to describe services in serving the library manager disabilities in school library (SLB) Batusangkar City; (2) to describe the obstacles faced in serving the library manager disabilities in school library (SLB) Batusangkar City; (3) to describe what efforts were made to overcome the obstacles encountered in serving the library manager disabilities in the school library (SLB) Batusangkar City. Data was collected through observation/ interview and literature study. Interviews with library managers and principals School (SLB) Batusangkar City. Data analysis be done in descriptive. Based on analyzing the data, it was concluded the following matters. First, the service manager in the service user library disabilities such as; (1) visually impaired;Â library managers to guide and give direction blind users according to the information he wants, (2) the Deaf; library management serving the deaf to communicate using sign language, manual communication, body language and lip. and, (3) quadriplegic, the library serves quadriplegic to help pick up a book or find the desired information. Second, the difficulties faced in serving the library manager disabilities in school library (SLB) Batusangkar City, namely: (1) the lack of facilities and infrastructure; (2) funds; (3) Human Resources (HR). And Third, the efforts of librarians in serving users, namely: (1) improve the infrastructure in the School library (SLB) Batusangkar City; (2) allocate 10% of funds available for building infrastructure in the School library (SLB) Batusangkar City; (3) adding a Human Resources (HR) educational background in library science.Â Keyword: disabilities, Batusangkar, school library.This paper discussed about the attitude in serving the library manager disabilities in school library (SLB) Batusangkar City. This study aims to: (1) to describe services in serving the library manager disabilities in school library (SLB) Batusangkar City; (2) to describe the obstacles faced in serving the library manager disabilities in school library (SLB) Batusangkar City; (3) to describe what efforts were made to overcome the obstacles encountered in serving the library manager disabilities in the school library (SLB) Batusangkar City. Data was collected through observation/ interview and literature study. Interviews with library managers and principals School (SLB) Batusangkar City. Data analysis be done in descriptive. Based on analyzing the data, it was concluded the following matters. First, the service manager in the service user library disabilities such as; (1) visually impaired;Â library managers to guide and give direction blind users according to the information he wants, (2) the Deaf; library management serving the deaf to communicate using sign language, manual communication, body language and lip. and, (3) quadriplegic, the library serves quadriplegic to help pick up a book or find the desired information. Second, the difficulties faced in serving the library manager disabilities in school library (SLB) Batusangkar City, namely: (1) the lack of facilities and infrastructure; (2) funds; (3) Human Resources (HR). And Third, the efforts of librarians in serving users, namely: (1) improve the infrastructure in the School library (SLB) Batusangkar City; (2) allocate 10% of funds available for building infrastructure in the School library (SLB) Batusangkar City; (3) adding a Human Resources (HR) educational background in library science.Keyword: disabilities, Batusangkar, school library.